CONSTRUCTION OF NEW MULTI-FUNCTION TYPE ARTIFICIAL BOUNDARY PILLAR FOR TRANSITION FROM OPEN PIT TO UNDERGROUND MINING - Honggang Ren; Zhuoying Tan; Panxue Feng (Civil Engineering Journal, 2019)
In allusion to the defects of large material consumption and high construction cost of conventional artificial boundary pillar for the transition from open pit to underground mining, a new multi-function type of artificial boundary pillar scheme of reinforced concrete is proposed, which creates favourable conditions for underground mining below the pillar and stacking tailings over the pillar. We established the mechanical model of the artificial pillar, and use MIDAS-FLAC3D software to analyse the stability of the artificial pillar. The result shows that the multifunctional artificial pillar has good impervious control and flood control characteristics and bearing capacity, and can effectively separate the influence between the open pit and the underground, which realizes the effective utilization of resources and greatly improve the economic efficiency of mines. At the same time, the tailings in the open pit will support the open slope and enhance the stability of the slope. Moreover, this method effectively reduces the area of tailings reservoir and has good ecological and environmental protection value, which can provide useful reference for related mines.